Recent Perceived Stress, Amygdala Reactivity to Acute Psychosocial Stress, and Alcohol and Cannabis Use in Adolescents and Young Adults With Bipolar Disorder - Le, Vanessa; Kirsch, Dylan E.; Tretyak, Valeria; Weber, Wade; Strakowski, Stephen M.; Lippard, Elizabeth T. C. (Frontiers in Psychiatry, 2021)
BACKGROUND: Psychosocial stress negatively affects the clinical course of bipolar disorder. Studies primarily focused on adults with bipolar disorder suggest the impact of stress is progressive, i.e., stress response sensitizes with age. Neural mechanisms underlying stress sensitization are unknown. As stress-related mechanisms contribute to alcohol/substance use disorders, variation in stress response in youth with bipolar disorder may contribute to development of co-occurring alcohol/substance use disorders. This study investigated relations between psychosocial stress, amygdala reactivity, and alcohol and cannabis use in youth with bipolar disorder, compared to typically developing youth. METHODS: 42 adolescents/young adults [19 with bipolar disorder, 23 typically developing, 71% female, agemean+SD=21+2 years] completed the Perceived Stress Scale (PSS), Daily Drinking Questionnaire modified for heaviest drinking week, and a modified Montreal Imaging Stress functional MRI Task. Amygdala activation was measured for both the control and stress conditions. Main effects of group, condition, total PSS, and their interactions on amygdala activation were modeled. Relationships between amygdala response to acute stress with recent alcohol/cannabis use were investigated. RESULTS: Greater perceived stress related to increased right amygdala activation in response to the stress, compared to control, condition in bipolar disorder, but not in typically developing youth (group x condition x PSS interaction, p=.02). Greater amygdala reactivity to acute stress correlated with greater quantity and frequency of alcohol use and frequency of cannabis use in bipolar disorder. CONCLUSION: Recent perceived stress is associated with changes in amygdala activation during acute stress with amygdala reactivity related to alcohol/cannabis use in youth with bipolar disorder.